Detection and Clinical Assessment of High-risk Groups for Periodontal Disease in a Longitudinal Study - SHIMABUKURO, Yoshio; OHTAKE, Tsuyoshi; SHIMAUCHI, Hidetoshi; KITAMURA, Masahiro; OKADA, Hiroshi; MIKI, Yasuo; MURAKAMI, Shinya (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1993)
This study was performed to detect patients at risk for future progression of periodontal disease and to examine the characterisitcs of such patients. Thirty-three subjects who had paticipated in an initial preparation and maintenance care program for five years after reevaluation were randomly selected. Clinical parameters were collected at the time of the baseline examination, re-evaluation examination and annual examinations during the maintenance phase. We defined deteriorated sites as sites with a greater than 2 mm increase in probing depth during the period of the study and a residual probing depth of more than 4mm at the examination five years after re-evaluation. The percentage of the deteriorated sites was calculated in each patient. The deterioration ratio ranged from 0% to 28.7%. Six patients (18.2%) had a deterioration ratio greater than 10%, and 57.7% of all deteriorative sites were concentrated in these patients. The outcome of clinical parameters in patients with high deterioration ratios was examined, but in the present study, no clinical parameter had the ability to predict patients at risk for future progression of periodontal disease.